Neighborhood Walkability and Sedentary Time in Belgian Adults - Van Dyck, Delfien; Cardon, Greet; Deforche, Benedicte; Owen, Neville; Sallis, James F.; De Bourdeaudhuij, Ilse (American journal of preventive medicine, 2010)
Sedentary behavior (too much sitting) has deleterious health consequences that are distinct from lack of physical activity (too little exercise). This study aimed to examine the associations of neighborhood walkability and sociodemographic factors with adults' self-reported and objectively assessed sedentary time. This Belgian cross-sectional study was conducted between May 2007 and September 2008. Twenty-four neighborhoods were stratified on GIS-based walkability and neighborhood SES. In all, 1200 adults (aged 20–65 years; 50 per neighborhood; 42.7 [SD=12.6] years; 47.9% men) completed a sociodemographic survey and the International Physical Activity Questionnaire. They also wore an accelerometer for 7 days: Sedentary time was identified as accelerometer counts of less than 100 per minute. Statistical analyses were performed in 2009, using multilevel regression models, adjusted for physical activity levels and individual SES. Residents of high-walkable neighborhoods reported more sitting time than those of low-walkable neighborhoods (439.8 vs 403.4 minutes/day of daily sitting time, p<0.05). Living in high-walkable versus low-walkable neighborhoods was also associated with 2.9% more accelerometer-measured overall sedentary time ( p<0.001). Being male, younger, unemployed, more highly educated, having a white-collar job (analysis for employed adults only), and living without children were all significantly associated with more sitting time. Contrary to expectations, living in a high-walkable neighborhood was associated with higher levels of sedentary time. If future studies in other contexts confirm these associations, environmental and policy innovations aiming to promote physical activity may need to address the potential negative health impact of sedentary behavior.